2015
DOI: 10.1038/ncomms7561
|View full text |Cite
|
Sign up to set email alerts
|

Targeting bacteria via iminoboronate chemistry of amine-presenting lipids

Abstract: Synthetic molecules that target specific lipids serve as powerful tools for understanding membrane biology and may also enable new applications in biotechnology and medicine. For example, selective recognition of bacterial lipids may give rise to novel antibiotics, as well as diagnostic methods for bacterial infection. Currently known lipid-binding molecules primarily rely on noncovalent interactions to achieve lipid selectivity. Here we show that targeted recognition of lipids can be realized by selectively m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 44 publications
3
93
0
Order By: Relevance
“…Recent publications from several groups including our own have shown that intermolecular iminoboronate formation is rapidly reversible under physiologic conditions with dissociation constants in the low mM range. 1822 We postulated that intramolecular iminoboronate formation should allow spontaneous and highly efficient cyclization of peptides. Importantly, cyclic peptides with iminoboronate linkages should be able to linearize in response to physiologic stimuli, therefore allowing facile control of their functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications from several groups including our own have shown that intermolecular iminoboronate formation is rapidly reversible under physiologic conditions with dissociation constants in the low mM range. 1822 We postulated that intramolecular iminoboronate formation should allow spontaneous and highly efficient cyclization of peptides. Importantly, cyclic peptides with iminoboronate linkages should be able to linearize in response to physiologic stimuli, therefore allowing facile control of their functions.…”
mentioning
confidence: 99%
“…Similarly, no cyclization was observed when an AB1 residue was placed adjacent to a lysine in peptide sequences. 22 Finally, the negative control peptide P11 (Fig. S15, SI), which presents a deborylated residue (AB4, Fig.…”
mentioning
confidence: 99%
“…We [3] and others [4] have shown that, in comparison to simple imines, [5] iminoboronates display much improved thermodynamic stability and allows labeling of biological amines at low millimolar concentrations (Scheme 1a, b). In this contribution, we extend our investigation of the iminoboronate chemistry to α-nucleophiles (Scheme 1c).…”
mentioning
confidence: 99%
“…The binding affinity of 2-APBA to acethydrazide was assessed by using UV-vis (Figure S2) and 1 H-NMR spectroscopy (Figure 1b), which yielded comparable dissociation constants in the sub-millimolar range ( K d : ~0.6 mM). In comparison to primary amines, which typically conjugate with 2-APBA at low millimolar concentrations, [3] acethydrazide displays a higher propensity for conjugation with 2-APBA. Similar behavior was observed for benzhydrazide, for which a K d value of 0.5 mM was obtained (Figure S3).…”
mentioning
confidence: 99%
See 1 more Smart Citation